Protection of taxpayer personal data in tax administration: a review - Judijanto, Loso (Digital Business: Tren Bisnis Masa Depan, 2024)
The protection of personal data in tax administration is a critical issue in the digital age. Tax authorities collect and process vast amounts of personal data from taxpayers, raising concerns about privacy and data security. This research explores the importance of safeguarding taxpayer privacy in tax administration. It examines the legal and regulatory frameworks governing personal data protection in the tax context, emphasizing the need for robust data security measures and transparent data handling practices. The study also discusses the potential consequences of data breaches and privacy violations, highlighting the importance of building trust between taxpayers and tax authorities. The research concludes by emphasizing the need for ongoing efforts to strengthen personal data protection in tax administration to ensure taxpayer privacy and maintain public confidence in the tax system